The Market Knowledge in the Industrial Markets: Dimensions and Conditions - Amina BENALI (Communications of International Proceedings, 2021)
This study aims at exploring "the industrial market knowledge" as a concept, according to the four dimensions, which are the consumer knowledge, the product knowledge, the competitor knowledge and the supplier knowledge. These dimensions are theoretically validated according to the several previous studies that have used the descriptive approach. The latter was found that the market knowledge is the most effective marketing tool that affects the industrial enterprise's performance in order to achieve a good perceptual reputation in the environment. Whilst the market knowledge achieves a great efficiency in the convergence between firms that enable the economies of scale.
Keywords: The Customer Knowledge; The competitor knowledge; The Producer Knowledge; The Supplier Knowledge.